La tente dans la ville, la mine dans la tente, le marketing dans le désert - Sofia Smyej (L’Année du Maghreb)
This article examines how the concepts of secularization (Meziane, 2022) and extractivism, as structuring processes, reconfigure subjectivities and nomadic lifestyles in the northwestern Sahara, a region marked by intensified extractive activities since the mid-20th century. Based on ethnographic research conducted in 2022 and 2023, it analyzes how the exploitation of natural resources transforms local socio-political structures towards forms of governance and integration within the postcolonial state as a historical process. Engaging with the theory of extraversion (Bayart, 1999), the article demonstrates how Sahrawi elites leverage relationships with external actors to strengthen their local power while maintaining complex connections with state structures. The article illustrates the complexity of transgenerational positionalities within a family belonging to the local elite, navigating between the transmission of the northwestern Saharan nomadic heritage and adaptation to neoliberal and rentier dynamics, which transforms power relations.